The impact of multiple insertions on peripheral intravenous access in low-birth-weight infants in perinatology - Rose Nirwana Handayani; Defi Efendi (PAGEPress Publications, 2021)
Low-Birth-Weight (LBW) infants have very small veins, and there is a risk of needing multiple insertions to establish peripheral intravenous access. This study aimed to examine the impacts of multiple insertions during peripheral intravenous access in LBW infants. This cross-sectional study involved 216 respondents. Data were analyzed with the Spearman correlation. The results showed a significant relationship (p<α) between multiple insertions to establish peripheral intravenous access to LBW infants with increased pain, heart rate, respiratory rate, duration of crying, delayed treatment, duration of insertion, and high cost of care (p<0.001; r=0.358-0.836). Meanwhile, multiple insertions might decrease oxygen saturation and body temperature (p<0.001; r=0.358). In this study, multiple insertions were correlated with several negative impacts on the physiological function and discomfort of LBW infants. The study also highlights the effect on time of treatment precision and cost effectiveness. Recommendation: It is necessary to develop preventive measures to reduce the impact of multiple insertions to establish peripheral intravenous access in LBW infants.